The Labor Market Structure of Transportation Sector in Indonesia: Digital Economy, Investment, Pandemic COVID-19, Job Creation Law - Suparna Wijaya (Gorontalo State University, 2021)
The development of the digital economy leads to the loss of several jobs and the emergence of new jobs. It also allows labor shifting between the new jobs and the old jobs. This phenomenon could raise the potential for unabsorbed labor which will cause unemployment problems. The COVID-19 pandemic, which requires large-scale social restrictions (PSBB), has certainly affected the transportation sector. This study aims to examine the influence of the digital economy, investment, the COVID-19 pandemic, and the Job Creation Law on the labor market structure of the transportation sector in Indonesia. The research method used is quantitative. The data used are the time series from January 2018 to November 2020. The results of this study indicate that the digital economy has no effect on the structure of the labor market in the transportation sector in Indonesia. Meanwhile, investment, the COVID-19 pandemic, and the Job Creation Law, respectively, have a significant effect on the structure of the labor market in the transportation sector in Indonesia. The impact of investment and the COVID-19 pandemic on the labor market structure of the transportation sector in Indonesia is negative. Meanwhile, the effect of the Job Creation Law on the labor market structure of the transportation sector in Indonesia is positive. Simultaneously, the digital economy, investment, the COVID-19 pandemic, and the Job Creation Law affect the labor market structure of the transportation sector in Indonesia.